Penghayatan Nilai Ajaran Samin dalam Membentuk Sikap Enterpreneurship pada Masyarakat Samin Klopodhuwur Kabupaten Blora - Kusuma, Aryanti Muhtar; Anjani, Reza Kurnia (Bisei : Jurnal Bisnis dan Ekonomi Islam, 2022)
The Samin Klopodhuwur community is a group of people who still choose a naturalist lifestyle in their lives, but have relevant and strong values and norms. The teachings inherited from the ancestors of the Samin people are still maintained and preserved. The purpose of this study is first to find out what Saminism values shape entrepreneurial attitudes. Second is to find out to what extent Samin's entrepreneurial value contributes to the economic welfare of the Samin community. This research is field research using the qualitative method with the phenomenological approach. Researchers conducted research on the Samin tribe in Klopodhuwur, Blora Regency, regarding the appreciation of Samin's teaching values, its role in shaping entrepreneurial attitudes. The data collection techniques used observation, interviews, and documentation for each informant who was the subject of the study. The results of this study indicate that, First Values of Saminism of the people of Kopodhuwur Village, Blora Regency, which are still firmly held in an entrepreneurial attitude, honest, independent, disciplined, friendly and keep promises. Second, by establishing the basic values of Samin's teachings such as being honest, independent, disciplined, friendly and keeping promises applied to entrepreneurial values, the Klopodhuwur village community already has performances in entrepreneurship to improve the economic welfare of the Samin people